A Clinico-Epidemiologic Study of Neurologic Associations and Factors Related to Speech and Language Delay - Parakh , Manish; Parakh , Poonam; Bhansali , Suman; Gurjar, Anoop Singh; Parakh, Priyanka; Mathur , Gagan; Gagan, Mathur (National Journal of Community Medicine, 2012)
Objectives: SLD is a significant neurodevelopmental complication and association of several neurologic disorders. The current study evaluates the neurologic associations and factors related to SLD. Methods: A one year retrospective study was done at Tertiary Care Center in India. Medical records of patients examined at Pediatric Neurology Clinic for SLD, between December 2009 and December 2010 were studied and the collected data was analyzed. Results: The prevalence of SLD was 16.27% and the Male : Female ratio was 2.76:1 in this study. GDD, Seizure disorder and ADHD were major comorbid conditions. Significant associations seen were; PIH, IUGR, Oligohyraminos, Perinatal- Neonatal resuscitation, LBW, LSCS, neonatal Icterus and seizures. There was a positive family history of SLD in 23.85% patients. EEG was epileptiform in 45.87% patients and features suggestive of Perinatal ABI due to varied etiology was the major neuroradiologic finding followed by congenital structural abnormalities. No specific diagnosis was possible in 33.94% patients, but 17.43% had Primary Epilepsy syndrome and 17.43% had a suspected Neurogenetic etiology. Conclusion: Exact etiological diagnosis of SLD is challenging & not possible on many occasions. Most important associations include seizure disorder, ADHD, autism, neonatal resuscitation and Epileptiform EEG with or without clinical seizure activity. Most of these patients have either an epilepsy syndrome or suspected Neurometabolic or Neurogenetic etiology.